JĘZYK I TOŻSAMOŚĆ W RODZINIE TRANSNARODOWEJ: STUDIUM PRZYPADKU - Wąsikiewicz-Firlej, Emilia (Neofilolog, 2018)
The following paper analyses child language socialization in a multilingual transnational family from the perspective of the emerging concept of family language policy (FLP). The central assumption of FLP is the crucial role of parents’ language ideologies in their children’s language socialization and construction of their widely-understood identity. The participants of the undertaken case study were three members of a Polish-Japanese family residing in the UK. The inquiry was based on a series of semi-structured interviews with individual family members and cyclical observation of the whole family over the period of 13 months. The results showed certain discrepancies between the language ideologies and practices of the parents, as well as difficulties in managing the family’s language policy that was to a large extent shaped by the child’s individual preferences and educational needs, often irrespective of the parents’ plans or intentions. Generally, the study reported essential difficulties in maintaining the child’s multilingualism due to a limited use of the minority languages (Japanese and Polish) at the cost of the majority language (English).